Carfilzomib, dexamethasone, and daratumumab versus carfilzomib and dexamethasone for patients with relapsed or refractory multiple myeloma (CANDOR): updated outcomes from a randomised, multicentre, open-label, phase 3 study. Issue 1 (January 2022) - Usmani, Saad Z; Quach, Hang; Mateos, Maria-Victoria; Landgren, Ola; Leleu, Xavier; Siegel, David; Weisel, Katja; Gavriatopoulou, Maria; Oriol, Albert; Rabin, Neil; Nooka, Ajay; Qi, Ming; et al.
Summary: Background: Despite recent advances in therapeutic options, there remains an unmet need for treating patients with relapsed or refractory multiple myeloma, especially in those previously exposed or refractory to lenalidomide. This updated efficacy and safety analysis from the phase 3 CANDOR study compared carfilzomib, daratumumab, and dexamethasone (KdD) with carfilzomib and dexamethasone (Kd) in patients with relapsed or refractory multiple myeloma. Methods: In this updated analysis of the randomised, multicentre, open-label, phase 3 CANDOR study, patients (aged ≥18 years) with relapsed or refractory multiple myeloma, at least a partial response to between one and three previous therapies, and Eastern Cooperative Oncology Group performance status of 0–2, were recruited from 102 medical centres globally and randomly assigned (2:1) by interactive voice or web response software to receive KdD or Kd. Participants were stratified by disease stage, previous proteasome inhibitor or anti-CD38 antibody exposure, and number of previous therapies. All patients received intravenous infusions of carfilzomib twice per week at 56 mg/m 2 (20 mg/m 2 on days 1 and 2 during cycle 1) on days 1, 2, 8, 9, 15, and 16 of each 28-day cycle. Daratumumab (8 mg/kg) was administered intravenously on days 1 and 2 of cycle 1 and at 16 mg/kg weekly for the remaining doses of the first two cycles, then every 2 weeks for four cycles (cycles 3–6), and every 4 weeks thereafter. Patients received 40 mg dexamethasone weekly (20 mg for patients >75 years old). This analysis was a preplanned interim analysis for overall survival; however, at the time of data cutoff, overall survival data were not mature. The primary endpoint was progression-free survival. Here, we provide updated progression-free survival data, assessed centrally by Onyx Response Computer Algorithm in the intention-to-treat population, with 11 months additional follow-up. Adverse events were assessed in the safety population, which included all participants who received at least one dose of trial treatment. CANDOR is registered with ClinicalTrials.gov, NCT03158688, and is active but not recruiting. Findings: Between June 13, 2017, and June 25, 2018, 466 patients were enrolled, of whom 312 received KdD and 154 received Kd. At data cutoff (June 15, 2020), median follow-up was 27·8 months (IQR 25·6–29·5) for KdD and 27·0 months (13·2–28·6) for Kd. Median progression-free survival was 28·6 months (95% CI 22·7–not estimable [NE]) in the KdD group and 15·2 months (11·1–19·9) in the Kd group (hazard ratio 0·59 [95% CI 0·45–0·78], log-rank p<0·0001). Treatment-emergent adverse events in the safety population were consistent with the primary analysis. Grade 3 or worse treatment-emergent adverse events occurred in 268 (87%) patients in the KdD group and 116 (76%) in the Kd group; most commonly thrombocytopenia (76 [25%] vs 25 [16%], respectively), hypertension (65 [21%] vs 23 [15%]), pneumonia (54 [18%] vs 14 [9%]), and anaemia (53 [17%] vs 23 [15%]). Serious adverse events occurred in 194 (63%) patients with KdD and 76 (50%) with Kd. Adverse events leading to death occurred in 27 (9%) patients in the KdD group and seven (5%) in the Kd group; most commonly septic shock (five [2%] vs one (1%]) and pneumonia (four [1%] vs none). No new treatment-related deaths have occurred since the primary analysis. Interpretation: A clear, maintained progression-free survival benefit of KdD over Kd with longer follow-up was confirmed, making KdD an emerging standard-of-care for patients with relapsed or refractory multiple myeloma. Funding: Amgen and Janssen.